Canning of "Dilis" (Stolephorus Commersoni) sardine style - Lalata, Lolita G.
ABSTRACT The study was directed towards the development of canned "dilis" sardine style. Factors studied involved acceptability of whole or headless "dilis", use of three types of oil, variations in the levels of tomato sauce, and addition of seasonings. Statistical analysis of the results of the subjective evaluation using the nine point hedonic scale and difference tests were made using analysis of variance and mean score. On the basis of the analysis of results for the different formulations evaluated, one was finally chosen. The specifications for the developed product were then set up based on the both subjective and objective tests. Analsis of crude protein, peroxide value, microbiological examination and heat penetration study were made. Cost accounting for the bench scale production of the canned "dilis" was presented together with price comparison of similar products available in the market.